Conflicting Tendencies in the Development of Scientific and Technical Language Varieties: Metaphorization vs. Standardization - Iļjinska, Larisa; Smirnova, Tatjana (Research in Language, 2014)
The present paper discusses relations between meaning and context as an interactive process that promotes cognition and communication, both intralingual and interlingual. The article also studies two evident conflicting tendencies in the development of technical language: metaphorization and standardization. Metaphorical meaning extension is characteristic of technical vocabulary in all discourse domains. At the same time, contemporary development of corpus linguistics facilitates standardization of terms. Taking into account pragmatic aspects of the text environment, i.e. referential, situational, cultural and social contexts, language users can interpret the meaning of new terms, establish relations and interconnections between terms and concepts within a text, domain and entire scientific and technical discourse. In the present article, observations on the nature and application of contemporary technical terminology are made on the basis of extensive empirical research.